APPLICATION OF AI IN THE CREATIVE PROCESS: CASE STUDY IN THE DESIGN INDUSTRY - Nugroho, Budi Sulistiyo; Annasit, Annasit; Hamid, Farid Alfalaki; Setiyono, Agus (Yayasan Adra Karima Hubbi, 2025)
The design industry has undergone significant transformations with the advent of Artificial Intelligence (AI), influencing the creative process in various ways. Despite its growing integration, the extent to which AI enhances creativity in design remains under-explored. This study aims to investigate the application of AI tools in the creative processes of designers, with a focus on identifying their impact on innovation, efficiency, and problem-solving. The research employs a qualitative case study approach, analyzing multiple design projects that incorporate AI tools, including generative design software and AI-driven prototyping systems. Data was collected through interviews with designers and observations of their workflows, supplemented by project outcome analyses. The results indicate that AI tools provide designers with new perspectives, automate repetitive tasks, and accelerate ideation, leading to increased productivity and innovative solutions. However, challenges such as the need for proper training and concerns about AI replacing human creativity were also noted. The study concludes that while AI enhances the creative process, it should be seen as a complement to human ingenuity rather than a replacement. Designers who effectively integrate AI tools into their workflows experience enhanced creativity, though a balance must be maintained between machine-driven processes and human judgment.